The influence of energy attenuating aircraft seats on lumbar spine burst fractures: an incident reconstruction. (2018) - Desmoulin, Geoffrey T.; Bird, Kevin G.; MacIntosh, Alexander R.
Many injuries from helicopter crashes are due to large vertical loads transferred from the ground, through the aircraft and to the spine of seated occupants. Helicopter manufacturers aim to reduce these loadings through energy-attenuating seats. This report details the methodology used to reconstruct an incident and determine the loads experienced by the passengers, specifically a passenger who sat in the rear right seat of the helicopter and suffered a lumbar burst fracture. (a) analysing the injury; (b) analysing damage to the seat to estimate impact forces, and (c) analysing the mechanism of failure of the landing strut to calculate the impact angle and validate the impact forces at the seat. Once the range of force experienced by the passenger was estimated, the effect of the choice of seat was investigated to determine if this injury could have been avoided using seats commercially available at the time of helicopter manufacturing.